AVERYL Theory™: Why PMO Transformation Fails—and How Risk Becomes the Catalyst for Strategic Renewal - Alin Veronika; Ir. Yusuf Latief; Leni Sagita Riantini (Journal of Project Management Research, 2025)
Project Management Offices (PMOs) have become a standard feature of contemporary organisations. Across industries—from infrastructure and construction to IT and the public sector—PMOs are expected to improve delivery discipline, strengthen governance, and translate strategy into execution. Yet despite their widespread adoption, PMO performance remains highly uneven. Many PMOs operate efficiently at an operational level but struggle to demonstrate sustained strategic value, while others undergo repeated restructuring without meaningful transformation.This white paper introduces AVERYL Theory™, a new conceptual lens for understanding why PMO transformation efforts often fail—and how they can succeed. Rather than viewing PMO development as a linear progression of maturity stages, AVERYL Theory reframes PMO transformation as a risk-activated organisational process shaped by internal capabilities, governance tensions, and strategic pressures.At the core of AVERYL Theory lies a counterintuitive insight: risk does not primarily weaken PMO performance; it activates transformation. When risk exposure exceeds organisational tolerance, it exposes structural misalignment and forces change. Transformation is therefore driven not by best practices or benchmarking alone, but by how organisations interpret and respond to risk signals embedded within their PMO systems.Written for executives, PMO leaders, and transformation sponsors, this white paper moves beyond tools, templates, and maturity models. It explains why traditional PMO transformation approaches fall short, how risk functions as a catalyst rather than a threat, and how PMO transformation can be reimagined as a mechanism for strategic renewal.AVERYL Theory™ offers not a single PMO design, but a system-level way of thinking that connects capability, risk, transformation, and performance.